Efektivitas Kompres Hangat Serai (Cymbopogon Citratus) dan Kompres Hangat Cengkih (Syzygium Aromaticum) terhadap Penurunan Nyeri Gout Arthritis di Desa Curahkalong Kecamatan Bangsalsari Kabupaten Jember - Misbah Misbah; Rizka Rizka; Yaqin Yaqin (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2024)
Joint shoreness is a symptom of gout arthritis caused by the presence of monosodium crystal deposits in the joints. The treatment to reduce pain from the shoreness is using lemongrass warm compresses and clove warm compresses. The purpose of this study is to analyze the effectiveness of lemongrass warm compress and clove warm compress on the reduction of gout arthritis pain in Curahkalong Village, Bangsalsari District, Jember Regency. This type of research is Quasy Experimental, two groups of pre test and post test design.The population was 107 gout arthritis using purposive sampling to find 36 respondents gout arthritis who had inclusion and exclusion criteria. Data collection uses a numeric pain scale (NRS) observation sheet. Statistical tests use the Wilcoxon and Mann-Whitney tests. The results of the research obtained a pain scale of 4.72 for the pre-test lemongrass group and 3.11 for the post-test. In the clove group, the pre-test was 4.78 and the post-test was 3.39. The results of the Wilcoxon test obtained a p-value of 0.000 in the lemongrass group and the clove group. The results of the Mann-Whitney test obtained different score between the two groups, a p-value of 0.270 with an average value of 20.19 in the lemongrass group and 16.81 in the clove group.